Предмет: Алгебра,
автор: Аноним
пожалуйста помогите решить уравнение( x-3^2)-(x-1)(x+1)+6x^2 при x=2,13 решите правильно
Ответы
Автор ответа:
0
x^2+9 -6x - x^2 +1 +6x= -6x +10 при х= 2,13:
-6*2,13 + 10= -2,78
-6*2,13 + 10= -2,78
Автор ответа:
0
( x-3)^2-(x-1)(x+1)+6x= x^2-6x+9-x-3x^2-x^2+x-x+6x= -3x^2+9 .
при x=2,13
-3*(2,13)^2+9=-4,61
при x=2,13
-3*(2,13)^2+9=-4,61
Похожие вопросы
Предмет: Алгебра,
автор: cicurinamarina62
Предмет: Другие предметы,
автор: azamatkalybaev88
Предмет: Биология,
автор: ungamos
Предмет: Алгебра,
автор: mazahaka1011